Én is voltam egykor joghallgató – Egy jogászélet főbb állomásai - Boleratzky, Lóránd (Gerundium, 2012)
I ALSO USED TO BE A STUDENT OF LAW: STAGES IN A JUROR’S LIFE. An authentic record, never before published, of the reminiscences of 92-year-old Loránd Boleratsky, a one-time scholar of evangelical church law and the last surviving privat-docent from the decades before 1950, pertaining to the cultural climate involving the academy of law in Miskolc and the relations surrounding the school of law in Debrecen. His reminiscences also include an account of his studies in Berlin and Helsinki, as well as his short-lived teaching career at the law academy in Miskolc. hrough a description of his increasingly more diicult fate in the 1950s we can gain an insight into the hostile relationship between the state and the church, the attacks of the atheist communist regime upon the churches, about the tragic fates of bishops József Mindszenthy, Lajos Ordas, and Zoltán Turóczy, all of them friends and colleagues of Loránd Boleratzky, one of the initiators and accomplishers of their rehabilitation.